The quantitative evaluation of information services - Petrikienė, Dalia Virginija (Knygotyra, 1988)
The author proposes using a quantitative criterion for evaluating information services—the extent to which information services meet the objective information requirements at all levels (state, branch, republic). The methods for analyzing reference information services according to this criterion, based on matrix theory, are presented, along with the results of analyses conducted in organizations and other institutions of the Lithuanian SSR. The article also offers recommendations for the development of reference information services.